Sustainable modification of stone column technique with polyethylene terephthalate (PET) plastic for strengthening the expansive clay - Ng, Jun Shen; Muzamir, Hasan (Yildiz Technical University, 2026)
This research investigated the modification of stone column application by the association of PET plastic as a coarse aggregate material for sustainable material replacement. Clay soil improvement with a granular material fabricated column substantially affected its soil-bearing capacity. Subsequently, it avoided severe problems such as soil settlement and structural instability. Previous studies have mentioned the function and alteration of stone columns using materials like bottom ash and fly ash. Still, no attention has been paid to the utilization of PET plastic for this area. This study examined the feasibility and reliability of materials, PET plastic, and kaolin clay S300 before examining geotechnical properties through their physical and mechanical characteristics. The fundamental geotechnical tests verified that kaolin clay was a problematic soil, and PET plastic was a substitute for coarse aggregate. Via the Unconfined Compression Test (UCT) approach, the highest improvement magnitude of soil recorded was at 17.38kPa or 48.42%, referring to the unreinforced kaolin specimen, which occurred at the GC10100 specimen. Coherently, it was suggested that the critical column penetrating ratio was 1.0. The research proposed that using PET plastic could act as a reinforcing component to rectify the engineering characteristics of kaolin.